Self organized nanostructures of amphiphilic block copolymers I - Müller, Axel H. E.; Borisov, Oleg.; Ballauff, M. (Matthias).; SpringerLink (Online service). (Berlin Springer, 2011)
Conformations and Solution Properties of Star-Branched Polyelectrolytes, by Oleg V. Borisov, Ekaterina B. Zhulina, Frans A. M. Leermakers, Matthias Ballauff and Axel H. E. Müller; Self-Assembled Structures of Amphiphilic Ionic Block Copolymers: Theory, Self-Consistent Field Modeling and Experiment, by Oleg V. Borisov, Ekaternia B. Zhulina, Frans A. M. Leermakers and Axel H. E. Müller; Interpolyelectrolyte Complexes Based on Polyionic Species of Branched Topology, by Dmitry V. Pergushov, Oleg V. Borisov, Alexander B. Zezin and Axel H. E. Müller; Co-assembly of Charged Copolymers as a Novel Pathway Towards Reversible Janus Micelles, by Ilja K. Voets, Frans A. Leermakers, Arie de Keizer, Marat Charlaganov and Martien A. Cohen Stuart; Fluorescence Spectroscopy as a Tool for Investigating the Self-Organized Polyelectrolyte Systems, by Karel Procházka, Zuzana Limpouchová, Filip Uhlík, Peter Ko?ovan, Pavel Matejícek, Miroslav ?tepánek, Mariusz Uchman, Jitka Kuldová, Radek ?achl, Jana Humpolícková, and M. Hof.
Electronic reproduction.
Keywords: Block copolymers; Nanostructures; Electronic books